Respuesta :

CcccccccccCcccc. Is the answer

Answer:  The correct option is

(A) -2x+7.

Step-by-step explanation:  We are given to find the additive inverse of the following expression :

[tex]E=2x-7.[/tex]

We know that

for any a, the additive inverse is given by b if a+b = 0.

Let y be the additive inverse of the given expression E.

Then, we must have

[tex]E+y=0\\\\\Rightarrow 2x-7+y=0\\\\\Rightarrow y=-2x+7.[/tex]

Thus, the required additive inverse of the given expression is -2x+7.

Option (A) is CORRECT.

ACCESS MORE